2011
DOI: 10.1103/physrevb.84.174512
|View full text |Cite
|
Sign up to set email alerts
|

Orbitally and magnetically induced anisotropy in iron-based superconductors

Abstract: Recent experimental developments in the iron pnictides have unambiguously demonstrated the existence of in-plane electronic anisotropy in the absence of the long-range magnetic order. Such anisotropy can arise from orbital ordering, which is described by an energy splitting between the two otherwise degenerate dxz and dyz orbitals. Including this phenomenological orbital order into a fiveorbital Hubbard model, we obtain the mean-field solutions where the magnetic order is determined self-consistently. Despite … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 65 publications
8
90
0
1
Order By: Relevance
“…Note that these results are insensitive to the microscopic mechanism behind the tetragonal symmetry breaking, i.e. whether it arises due to orbital [28][29][30][31][32][33][34][35] or spin fluctuations 2,36-40 , or electron-phonon coupling. In making quantitative comparison with experiments, an important issue is the presence of twin domains, i.e.…”
Section: Comparison To First-principle Calculations and Arpes Exmentioning
confidence: 99%
“…Note that these results are insensitive to the microscopic mechanism behind the tetragonal symmetry breaking, i.e. whether it arises due to orbital [28][29][30][31][32][33][34][35] or spin fluctuations 2,36-40 , or electron-phonon coupling. In making quantitative comparison with experiments, an important issue is the presence of twin domains, i.e.…”
Section: Comparison To First-principle Calculations and Arpes Exmentioning
confidence: 99%
“…Fermisurface anisotropies arising, for instance, from the ferroorbital order triggered at the nematic transition, affect mostly the Drude weight [11][12][13]. Anisotropic scattering, can be due to elastic processes, such as the development of local magnetic order around an impurity [14,15], or inelastic processes, such as the scattering of electrons by anisotropic magnetic fluctuations [16,17] known to exist below T s [18].…”
mentioning
confidence: 99%
“…Recent bulk transport and scattering measurements have suggested that the nematic phase is driven by electronic, rather than lattice, degrees of freedom [4][5][6][7][8] and is observed in all electronic channels -charge 9,10 , orbital 4 , and spin 7,11 . Spin order and spin fluctuations [12][13][14][15][16] (which couple quadratically to nematicity) as well as orbital order 17,18 and orbital fluctuations 19 (which can couple linearly) have been invoked to explain the nematicity.However, the dominant interaction responsible for the nematic ordering and fluctuations remains 2 unknown and identifying it is a key experimental goal. In this paper, we use variable temperature scanning tunneling spectroscopy to provide new insights into this issue by showing that our spectroscopic signals reveal that nematicity occurs in conjuction with strong antiferroic fluctuations and that both phenomena persist up to temperatures much greater than the temperatures at which longrange order is established.…”
mentioning
confidence: 99%